Herbage yield and quality of Gliricidia sepium under different cutting heights and defoliation frequencies - Tarawali, G.; Iji, P.A.; Chionuma, P.C.; Obot, U. (Springer, 1996)
The browse shrub Gliricidia sepium, introduced into the subhumid zone of Nigeria to serve as a supplementary-forage source for ruminant during the dry season, has the undesirable characteristic of shedding its leaves during its flowering phase which coincides with the early dry season. This report relates a management practice undertaken to maintain G. sepium in vegetative growth through the dry season. Evaluation was undertaken on the influence of cutting to different heights and defoliation at different frequencies. Eight different accessions of the species were involved in the study. Cutting generally ensured vegetative growth during the early dry season, with greater shoot development observed at a cutting height of 0.7 m than at two lower heights. Under the double harvest regime, dry matter yield was generally highest at first harvest and significantly (P<0.05) so at a cutting height of 0.3 m than at 0.5 or 0.7 m. Accession HYB yielded more dry matter than three other accessions harvested once. Cutting to 0.7 m yielded more leaves than cutting at lower heights. The foliage contained adequate levels of organic matter, crude protein and the minerals, Ca and P while the accession HYB consistently maintained a higher dry matter yield than the other accessions.